2010
DOI: 10.1002/evan.20251
|View full text |Cite
|
Sign up to set email alerts
|

The 10kTrees website: A new online resource for primate phylogeny

Abstract: Luke Matthews is an anthropologist and primatologist whose interests include the evolution of primate behavior, primate traditions, and human cultural evolution. He has conducted primatological fieldwork in Ecuador and Argentina. He employs phylogenetics, network analysis, and cluster analysis to study inheritance systems that range from DNA sequences to primate foraging traditions and human material culture. Importantly, the 10,000 trees that we provide are not random, but instead use recent systematic method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
564
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 597 publications
(580 citation statements)
references
References 68 publications
14
564
0
2
Order By: Relevance
“…Reproductive lifespan was calculated as age of sexual maturity subtracted from maximum longevity. Comparative datasets were matched to a dated consensus phylogeny for 301 primate species (10kTrees version 3, using GenBank taxonomy) (65). Taxonomic mismatches were resolved using the 10kTrees Translation table and the International Union for Conservation of Nature (IUCN) Red List website (66).…”
Section: Methodsmentioning
confidence: 99%
“…Reproductive lifespan was calculated as age of sexual maturity subtracted from maximum longevity. Comparative datasets were matched to a dated consensus phylogeny for 301 primate species (10kTrees version 3, using GenBank taxonomy) (65). Taxonomic mismatches were resolved using the 10kTrees Translation table and the International Union for Conservation of Nature (IUCN) Red List website (66).…”
Section: Methodsmentioning
confidence: 99%
“…Several traits have been found to affect parasitism, such as population density, geographic range size, group size, body mass, and diet (19). We explored whether these traits also covary with centrality of the primates using phylogenetic generalized least squares (PGLS) models (26) with the primate consensus dated tree from the 10kTrees Project (27). In a model with multiple predictor variables, we found that primates with denser populations living in larger groups and having broad distributions were more central [population density: estimate ± 1 SE = 0.32 ± 0.15, t = 2.10, P = 0.04; geographic range size: estimate ± 1 SE = 0.28 ± 0.14, t = 1.95, P = 0.05; group size: estimate ± 1 SE = 0.36 ± 0.17, t = 2.08, P = 0.04, R 2 = 0.490; PGLS with phylogenetic signal (λ) = 0.138, P = 0.06 compared to a model with λ = 0, n = 122 primates].…”
Section: Resultsmentioning
confidence: 99%
“…We used the 10kTrees dated phylogeny v. 3 with the associated taxonomy from GenBank [57]. We estimated phylogenetic signal in each trait using Blomberg's K and Pagel's l (see §1), with the picante [28] and phytools packages [31], respectively, in R [58].…”
Section: Phylogenetic Signal In Primate Traitsmentioning
confidence: 99%